Dataset_school_level_risk_factors_bullyvictims. - Quintana-Orts, Cirenia Luz; Mora-Merchán, Joaquín A.; Muñoz-Fernández, Noelia; Del-Rey, Rosario (Universidad de Málaga, 2024)
Considering the increasing rates of bullying in adolescence, more empirical evidence on how multiple factors work together in relation to the bully-victim role is needed. This study aims to explore individual and perceived school-level factors associated with the bully-victim role in the context of traditional bullying and cyberbullying, based on the social-ecological model. Factors such as aggressive conflict resolution, normative adjustment, emotional dysregulation, peer social network, teacher apathy, teacher support, and school connectedness were analyzed. Gender differences were also examined. Participants were 854 students (402 girls) between 11 and 18 years of age (M = 13.65; SD = 1.36) from four secondary schools. Results indicated common factors associated with the bully-victim role in both traditional bullying and cyberbullying, such as aggressive conflict resolution, normative adjustment, and school connectedness. Whereas higher teacher support was associated with the bully-victim role in traditional bullying, lower peer social network was associated with the cyberbully-victim role. Gender interaction effects were found in traditional bullying, with the likelihood of being a bully-victim being higher for girls with higher levels of teacher support and lower school connectedness. Our results highlight that individual factors affect bully-victims in traditional bullying and cyberbullying, and act in concert with perceived environmental conditions in the education context. Discipline and norm adjustment, as well as socio-emotional competencies such as emotional regulation and adequate conflict resolution, are important for preventing bully-victim involvement. Key factors in the school context to prevent double-role involvement are discussed.
Keywords: Acoso moral en la escuela; Adolescentes - Psicología; Aggressiveness victims; Victimization; Aggression; Ecological approach; School-level factors; Adolescence